2020
DOI: 10.21203/rs.3.rs-18296/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of glucose variability with postoperative delirium in acute aortic dissection patients: an observational study

Abstract: Background Blood glucose variability is associated with poor prognosis after cardiac surgery, but the relationship between glucose variability and postoperative delirium in patients with acute aortic dissection is unclear. The aim of this study is to investigate the association of blood glucose variability with postoperative delirium in acute aortic dissection patients. Methods We prospectively analyzed 257 patients including 103 patients with delirium. The patients was categorized into two groups according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Patients with severe illness and organ dysfunction may face a higher risk of developing delirium and indicating that delirium was associated with serious conditions. is study identifies sedative drugs use as precipitating factors as reported in prior studies [18,[38][39][40][41].…”
Section: Discussionmentioning
confidence: 85%
“…Patients with severe illness and organ dysfunction may face a higher risk of developing delirium and indicating that delirium was associated with serious conditions. is study identifies sedative drugs use as precipitating factors as reported in prior studies [18,[38][39][40][41].…”
Section: Discussionmentioning
confidence: 85%